2006
DOI: 10.1016/j.rmed.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and disease control of asthmatic patients in Flanders: A cross-sectional community pharmacy study

Abstract: The aim of this study was to describe medication use and disease management of asthmatic patients and to evaluate the usefulness of the Asthma Control Test (ACT) in community pharmacies. In 54 Flemish community pharmacies 166 asthmatic patients were included in the study. At inclusion, the study persons completed a survey to assess subject characteristics, symptoms and asthma attacks, and peak expiratory flow (PEF) was measured. Furthermore, the actual level of asthma control was assessed by ACT, a clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 16 publications
0
25
2
2
Order By: Relevance
“…The ACT was shown to be an excellent tool to measure rapidly [17] and accurately [20] the asthma control of patients presenting at community pharmacies, enabling the pharmacist to provide each patient with specific advice tailored to his/her clinical needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACT was shown to be an excellent tool to measure rapidly [17] and accurately [20] the asthma control of patients presenting at community pharmacies, enabling the pharmacist to provide each patient with specific advice tailored to his/her clinical needs.…”
Section: Discussionmentioning
confidence: 99%
“…correct inhalation technique and good medication adherence). To ensure that the intervention agreed with the new GINA guidelines, the Asthma Control Test1 (ACT; Quality Metric, Lincoln, RI, USA) was used as a rapid and easy tool to determine the level of asthma control of patients presenting at community pharmacies and to provide targeted pharmacist advice (table 1) [17]. The present randomised controlled trial was set up to study the hypothesis that such pharmacist intervention, focused on the optimal use of asthma medication and tailor-made to the patient's current asthma control, would result in an improved asthma control in adult patients over a 6-month period.…”
mentioning
confidence: 99%
“…The existing studies conducted in pharmacies mainly assess the control level of asthma and, in general, poor asthma control. [21][22][23] Identifying patients with poor ARA control may be the first step to helping patients obtain adequate treatment and to optimizing disease control.…”
Section: What Is Already Known About This Subjectmentioning
confidence: 99%
“…23 Another study, conducted via patient questionnaire at 54 pharmacies in Flanders, showed a high percentage of insufficiently controlled asthmatic patients, as assessed by patient responses and peak expiratory flow rate. 21 A study carried out in Portugal evaluated the degree of asthma control with a self-reported diagnosis and concomitant asthma therapy using ACT. The authors found a high degree of uncontrolled asthma, especially in older patients and, in general, a blunted perception of disease control.…”
Section: Limitationsmentioning
confidence: 99%
“…As highlighted by other reports (28,29) asthma in the elderly is not a rare disease, and its detection and management in that specific population deserves the highest consideration. Furthermore, the treatment choices should be carefully evaluated was prevalent (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Therefore, it is conceivable that a worse control of asthma is more common in younger ages.…”
Section: Discussionmentioning
confidence: 99%